Nanonization of a chemically synthesized flavone HMDF (3-hydroxy-3′, 4′-methylenedioxyflavone) by entrapping within calcium phosphate nanoparticles and exploring its antioxidant role on neural cells in vitro and zebrafish in vivo. (16th March 2021) - Patra, Mousumi; Banik, Milon; Bandopadhyay, Pathikrit; Dutta, Debanjan; Mukherjee, Riya; Das, Sreeparna; Begum, Naznin Ara; Basu, Tarakdas
Abstract: The chemical synthesis of 3-hydroxy-3′, 4′-methylenedioxyflavone (HMDF) was reported to generate a modified flavone of potent antioxidant activity with significant neuropharmacological properties. In this study, HMDF was nanonized by entrapping within calcium phosphate nanoparticles (CPNPs). HMDF-CPNPs were of (i) size 25 nm, (ii) zeta potential (−) [22 ± 3] mV and (iii) entrapment efficiency 67%. HMDF-CPNPs, but not HMDF alone, inhibited the in vitro activity of acetylcholinesterase enzymes to break down the major neurotransmitter compound acetylcholine. Moreover, nanonized HMDF had more antioxidant activity than bulk HMDF, as observed from its ability to protect mouse neural (N2A) cells from oxidative damage caused by H2 O2 exposure at the levels of cell viability, intracellular reactive oxygen species, mitochondrial membrane potential, cell cycle stages, nuclear integrity and neural connectivity. An in vivo study on zebrafish larvae ( Denio rerio ) also demonstrated that H2 O2 -mediated larval death was checked by HMDF-CPNP treatment. These results, therefore, suggest that HMDF-CPNPs may be developed as a potential antioxidant, particularly as a neuroprotectant.